Evaluation of Physical and Mechanical Properties for Hydrogel Wound Dressing Made of Commercial Aloe Vera and Sea Cucumber Gel - ANASTASIA MICHELLE, JAJAH (Universiti Malaysia Sarawak, 2022)
There are various types of wound dressing on the market. The wound dressing is limited in its absorbency ability, non-optimal mechanical stability, does not provide a soothing effect on the wound area, and the expensive cost. Therefore, the main objective of this research is to investigate the physical and mechanical properties of hydrogel wound dressing made by using commercial Aloe Vera gel and sea cucumber gel. Two categories of wound dressing are fabricated which is the wound dressing dried at 30 ℃ and 50 ℃. Whereas each category consisted of four different types of hydrogels wound dressing which are the Aloe Vera hydrogel, sea cucumber hydrogel, mixed hydrogel (Aloe Vera and sea cucumber), and pure gelatine hydrogel. The first part of the study involves fabricating all these four types of hydrogels wound dressing with a different composition of the raw material. The raw material used includes Aloe Vera gel, sea cucumber gel, glycerine, gelatine, and distilled water. The samples are fabricated through an open moulding process. Then, 4 types of tests are conducted which are the fluid intake capacity test, tensile test, thermal conductivity test and morphology evaluation. The fluid intake capacity test is done according to the standard of BS EN 13726-1. The samples are immersed in pseudo-wound exudate and deionized water for 30 minutes at 37 ℃. The test results indicate that the fluid intake capacity of samples dried at 50 ℃ is higher compared to the samples dried at 30 ℃ ranging from 39% to 88% and 61% to 99% after immersion in pseudo-wound exudate and deionized water respectively. In addition, sea cucumber hydrogel dried at 50 ℃ is found to have the highest fluid intake capacity after immersion in both test solutions. However, the hydrogels experience degradation behaviour. The fluid intake capacity is strongly dependent on the network structure within the samples and medium’s pH level. Moreover, the tensile properties of hydrogel wound dressing are tested according to ASTM D638-98. The tensile test is conducted to obtain the elongation at break, tensile strength, and Young’s Modulus of the wound dressing. The tensile test results signify that the samples dried at 50 ℃ have the highest value when compared to the samples dried at 30 ℃ ranging from 70% to 279%, 133% to 383% and 33% to 189% for the elongation at break, tensile strength and Young’s Modulus of the hydrogels respectively. In addition, the effective crosslinking by mixed (AV/SC) samples dried at 50 ℃ resulted in the greatest mechanical properties of 278.66%, 1.930 ± 0.316 MPa and 0.304 ± 0.017 MPa for the elongation at break, tensile strength, and Young’s Modulus respectively. Whereas the addition of excessive Aloe Vera gel causes the lower mechanical properties. The density measurement is taken for the thermal conductivity test samples. The lower drying temperature contributes to the higher amount of fluid within the samples, thus resulting in greater weight and density. Based on the observation, the samples dried at 30 ℃ are having the highest density which ranged from 6% to 11% when compared to the samples dried at 50 ℃. Meanwhile, the samples dried at 50 ℃ experiencing weight and height reduction which led to the lower density measurement. Thermal conductivity is measured according to ASTM E1225-99. Hydrogel wound dressing dried at 30 ℃ shows the highest thermal conductivity compared to the samples dried at 50 ℃ ranging from 6.500 W/mK to 7.600 W/mK. The morphology structure is evaluated by using Scanning Electron Microscope (SEM) Model 3030 Hitachi at a voltage of 5kV in a vacuum environment with different magnifications. Both samples dried at 30 ℃ and 50 ℃ have the same morphology structure. The lump of Aloe Vera gel, crack, air bubbles, and gelatine powder particles are seen within the samples.